Effect of strain rate on the mechanical properties of carbon/epoxy composites under quasi-static and dynamic loadings. (July 2016) - Li, Xin; Yan, Ying; Guo, Licheng; Xu, Chenghai
Abstract: Experimental investigations on warp-knitted and plain weave carbon fabric composites were made under quasi-static and dynamic strain rates, which mainly focused on the effect of strain rate on the tensile and compressive strength of the composite. The strain rate was 0.5 s −1 for quasi-static tests performed on a universal testing machine, whereas it ranged from approximately 200 s −1 to 2300 s −1 for the dynamic testing. The test results show that the tensile strength increased with increasing strain rate for both types of fabrics, whereas the effect of strain rate was negligible for the compressive strength. Also, the failure mechanism was characterized by examining the fracture surfaces using optical and scanning electron microscopy (SEM).